DEVELOPMENT OF FLIPPING BOOK LEARNING MATERIALS INTEGRATED WITH PROBLEM-BASED LEARNING TO IMPROVE STUDENTS' DIGITAL LITERACY - Delima, Cicci Ima; Rohman, Fatchur; Muntholib, Muntholib; Maasawet, Elsje Theodora (Universitas Tanjungpura, 2024)
Digital literacy is the ability to access, manage, understand, evaluate and create information safely and appropriately. This research aims to produce a valid, practical and effective problem-based learning flipping book instructional material focusing on the diversity of mangrove species, Gonda Mangrove Park, Polewali Mandar to increase student